Gene Signature–Based Approach Identified MEK1/2 as a Potential Target Associated With Relapse After Anti-TNFα Treatment for Crohn's Disease. Issue 6 (13th April 2018) - Gamo, Kanae; Okuzono, Yuumi; Yabuki, Masato; Ochi, Takashi; Sugimura, Kyoko; Sato, Yosuke; Sagara, Masaki; Hayashi, Hiroki; Ishimura, Yoshimasa; Nishimoto, Yutaka; Murakawa, Yusuke; Shiokawa, Zenyu; et al.
Abstract: Background: Anti–tumor necrosis factor alpha (anti-TNFα) therapy has become the mainstay of therapy for Crohn's disease (CD). However, post-therapy, the recurrence rate is still high. The aim of this study was to dissect the molecular mechanism for recurrence of CD treated with anti-TNFα therapy and investigate novel therapeutic options that could induce complete remission. Methods: We re-analyzed publicly available mucosal gene expression data from CD patients pre– and post–infliximab therapy to extract the transcriptional differences between responders and healthy controls. We used a systematic computational approach based on identified differences to discover novel therapies and validated this prediction through in vitro and in vivo experimentation. Results: We identified a set of 3545 anti-TNFα therapy-untreatable genes (TUGs) that are significantly regulated in intestinal epithelial cells, which remain altered during remission. Pathway enrichment analysis of these genes clearly showed excessive growth state and suppressed terminal differentiation, whereas immune components were clearly resolved. Through in silico screening strategy, we observed that MEK inhibitors were predicted to revert expression of genes dysregulated in infliximab responders. In vitro transcriptome analysis demonstrated that selective MEK1/2 inhibitor significantly normalized reference genes from TUGs. In addition, in vitro functional study proved that MEK1/2 inhibitor facilitated intestinal epithelial differentiation. Finally, using murine colitis model, administration of MEK1/2 inhibitor significantly improved diarrhea and histological score. Conclusions: Our data revealed the abnormalities in anti-TNFα responders' CD colons that would be cause of recurrence of CD. Also, we provided evidence regarding MEK1/2 inhibitor as a potential treatment against CD to achieve sustainable remission.